Vaccine strategies: Optimising outcomes. Issue 52 (20th December 2016) - Hardt, Karin; Bonanni, Paolo; King, Susan; Santos, Jose Ignacio; El-Hodhod, Mostafa; Zimet, Gregory D.; Preiss, Scott
Highlights: Many components must come together for delivery of effective immunisation services. Less developed countries may lack the appropriate healthcare infrastructure. Vaccination strategies must be feasible and acceptable to the target population. Experience and research have shown which vaccine strategies work well. Tailored, culturally-appropriate local approaches usually encourage success. Abstract: Successful immunisation programmes generally result from high vaccine effectiveness and adequate uptake of vaccines. In the development of new vaccination strategies, the structure and strength of the local healthcare system is a key consideration. In high income countries, existing infrastructures are usually used, while in less developed countries, the capacity for introducing new vaccines may need to be strengthened, particularly for vaccines administered beyond early childhood, such as the measles or human papillomavirus (HPV) vaccine. Reliable immunisation service funding is another important factor and low income countries often need external supplementary sources of finance. Many regions also obtain support in generating an evidence base for vaccination via initiatives created by organisations including World Health Organization (WHO), the Pan American Health Organization (PAHO), the Agence de Médecine Préventive and the Sabin Vaccine Institute. Strong monitoring and surveillance mechanisms are also required. An example is the efficient and low-cost approaches for measuring the impact of the hepatitis B control initiative and evaluating achievement of goals that have been established in the WHO Western Pacific region. A review of implementation strategies reveals differing degrees of success. For example, in the Americas, PAHO advanced a measles-mumps-rubella vaccine strategy, targeting different population groups in mass, catch-up and follow-up vaccination campaigns. This has had much success but coverage data from some parts of the region suggest that children are still not receiving all appropriate vaccines, highlighting problems with local service infrastructures. Stark differences in coverage levels are also observed among high income countries, as is the case with HPV vaccine implementation in the USA versus the UK and Australia, reflecting differences in delivery settings. Experience and research have shown which vaccine strategies work well and the factors that encourage success, which often include strong support from government and healthcare organisations, as well as tailored, culturally-appropriate local approaches to optimise outcomes. Author Video: Author Video Watch what authors say about their articles